Comparative Study Of Well Logs On The Mexia Type Of Structure - Frederic Lahee (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1925)
THE purpose of this paper is to demonstrate the similarity of the oil-producing structures in the Mexia1 fault zone, and to show how the apparently very irregular well logs in these fields may be used for the practical interpretation of subsurface conditions. The Mexia oil field, in Limestone County, Tex. (Fig. 1) is closely associated with a fault that trends about 30° east of north and has a displacement of between 200 and 400 ft., with downthrow on the west. Minor slips accompany this major fault, some being roughly parallel to the main break while others are transverse to it. These faults belong to the so-called Mexia fault zone, a belt of fracturing that has been traced in its characteristic features southward to near Kosse, 15 miles south of Groesbeck, in southern Limestone County, and northward at least as far as the Trinity river at the eastern border of Navarro County, and possibly as far north as Hunt and Hopkins counties.2 The Balcones fault zone, from 30 to 40 miles west of the Mexia fault zone, differs from the latter in that its principal displacement is a down-throw on the east. In this respect, it is exactly the opposite of the Mexia displacement. Between these two zones of major faulting lies a great down-dropped block, or graben, which is broken by numerous minor faults.